Determination of critical factors in the supply chain management of palmyra crafts using SWOT-AHP - Ezar Amrullah; Purwanto Purwanto; Rahayu Praya Ningsih (Universitas Pendidikan Nasional, 2024)
This study analyzed the critical factors in the supply chain management of the Palmyra handicraft industry in Central Lombok, Indonesia, using a SWOT-AHP methodology. The research aimed to identify strategic directions to enhance the industry's development by addressing strengths, weaknesses, opportunities, and threats. The findings highlighted key strengths such as increasing product demand, availability of raw materials, and high product quality. Conversely, weaknesses included limited financial capital, inadequate marketing capabilities, and the absence of a centralized production facility. Opportunities identified encompassed access to partnerships and capital, institutional support, and the application of appropriate technologies. However, threats such as raw material scarcity, declining interest among artisans, and rising supply chain costs posed significant challenges. The research concluded that prioritizing strengths and addressing critical weaknesses were vital for sustaining and growing the Palmyra handicraft industry. These insights provided actionable strategies for stakeholders to enhance competitiveness and operational efficiency.